Improving resident education through unstable chicken hips: a novel way to teach an infant hip examination. Issue 2 (6th July 2020) - Geswell, Matthew; Sinha, Neha; Mandel, Mark; Wheatley, Benjamin; Mirenda, William; Seeley, Mark
Abstract : Current clinical screening for infantile hip dysplasia relies on combined Ortolani and Barlow maneuvers, which have a quoted sensitivity and specificity of 74–98 and 84–99%, respectively. Teaching this delicate physical examination maneuver is difficult as it requires a distinct tactile feel. The purpose of this study is to validate a benchtop learning grocery-bought chicken simulator model of newborn hip instability through a pre- and post-test surveys. This model of hip dysplasia uses whole chickens. A posterior capsulotomy of the chicken's hip joint was performed to create instability. Provocative maneuvers to dislocate and relocate the hip were taught by a pediatric orthopedic surgeon. All participants completed an anonymous pre- and post-training surveys. A total of 58 participants were included in the study: 10 medical students, 13 pediatric residents, 15 orthopedic residents, and 20 orthopedic or pediatric attending physicians. The pediatric residents had performed the Barlow/Ortolani tests more than the orthopedic residents (96.15 ± 83.19 vs. 37.53 ± 60.89; P = 0.01); however, fewer pediatric residents reported feeling a positive examination (31 vs. 67%). The majority of the group agreed that the simulation felt and moved like an infant's hip (3.95 and 4.13; Likert five-point scale). The participants unanimously agreed that the model could be used to teach someone new to pediatrics the basic steps of the examination (4.91; Likert five-point scale) and should be implemented in the teaching curriculum (100%). The current study validates the benchtop model in teaching the clinical steps in detecting hip dysplasia. The model improved confidence and comfort level for all participants and proved to be a valuable tool for resident education in multiple specialties. By improving education with this model, we hope to improve early identification of hip dysplasia with increased accuracy across subspecialties.